2011
DOI: 10.1007/s00167-011-1852-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined gracilis tendon autograft reconstruction and discus repair of a chronic anterior–superior sternoclavicular joint dislocation

Abstract: A case of an 18-year-old gardener who sustained an anterior-superior dislocation of the sternoclavicular joint while playing handball and falling on his right shoulder is presented. Non-surgical treatment failed, and the patient could willingly dislocate the right clavicle while abduction and external rotation of the arm. This painful condition was finally treated with surgical reconstruction of the sternoclavicular joint using gracilis tendon autograft and repair of the discus. Level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
0
18
0
4
Order By: Relevance
“…Several techniques for reconstructing the sternoclavicular joint have been introduced, including fixation with plates, fixation with anchors, fixation of the capsule and joint disk, reconstruction in a “figure of eight” using a graft from an autologous tendon and reconstruction using a graft from the sternocleidomastoid fascia. 1 , 4 , 15 Resection of the medial portion of the clavicle has also been reported. The ideal treatment still remains unknown, given that few studies have presented long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques for reconstructing the sternoclavicular joint have been introduced, including fixation with plates, fixation with anchors, fixation of the capsule and joint disk, reconstruction in a “figure of eight” using a graft from an autologous tendon and reconstruction using a graft from the sternocleidomastoid fascia. 1 , 4 , 15 Resection of the medial portion of the clavicle has also been reported. The ideal treatment still remains unknown, given that few studies have presented long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…O tratamento ideal permanece desconhecido, já que há poucos estudos com resultados em longo prazo. Friedrich et al 15 submetidos a reconstrução da AEC com o enxerto entrelaç ado em "oito" através de túneis pré-perfurados. Poucos estudos relataram vantagem na reconstrução em "oito" relacionada a estabilidade primária.…”
Section: Discussionunclassified
“…12,14,15 Enxertos autólogos são usados a fim de evitar o riscos de infecção e para facilitar a integração do tecido, com o objetivo de um resultado positivo em longo prazo. Entre enxertos autólogos, acreditamos que o tendão do grácil e o do palmar longo, como por nós usado, sejam os ideais, pois o seu diâmetro resulta em menor morbidade.…”
Section: Discussionunclassified
“…3,5,6 Numerous techniques are available for reconstruction of the SC joint in patients with anterior instability; however, a gold standard technique has yet to be defined owing to numerous described techniques and low levels of evidence. 4,[6][7][8][9][10][11][12][13][14][15] A biomechanical study by Spencer and Kuhn 16 suggested that SC joint reconstruction using a free tendon graft oriented in a figure-of-eight fashion is superior to other methods when comparing load-to-failure and the reestablishment of normal anatomy. It is therefore theorized that figure-of-eight SC joint reconstruction with tendon graft should result in improved clinical outcomes and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%